Modeling the mobility of glyphosate from two contrasting agricultural soils in laboratory column experiments. Issue 7 (3rd July 2019) - Berzins, Andrejs; Jansons, Martins; Kalneniece, Kristine; Shvirksts, Karlis; Afanasjeva, Kristine; Kasparinskis, Raimonds; Grube, Mara; Bartkevics, Vadims; Muter, Olga
Abstract: Glyphosate (GLP) currently is one of the most widely used herbicides worldwide. The persistence of GLP and its major metabolite, aminomethylphosphonic acid (AMPA) in the environment has been described by other authors. This study was aimed at comparing the GLP and AMPA behavior in sandy and loamy sand soils after spiking with enhanced (445 µg g −1 ) concentrations of GLP in herbicide KLINIK ® (Nufarm, Austria) and bioaugmentation followed by 40 days weathering and a consistent three-stage leaching in a laboratory column experiment. Soil samples were obtained from mineral topsoil (0–10 cm) within former agricultural lands where soil parent material was formed by glacigenic deposits. The total amount of GLP and AMPA collected during three leaching stages was significantly ( p <.05) higher from columns with sandy soil, compared to loamy sand soil. Bioaugmentation resulted in considerably lower concentrations of AMPA in leachates, especially in the sets with sandy soil ( p =.01). Leachates were tested using FTIR spectroscopy and Daphnia magna . Statistical analysis of the changes in Ntot, Ctot, K +, Mg 2+, Al 3+, Ca 2+, Mn 2+ and Fe 3+ concentrations in soils after the leaching experiment revealed that the loamy sand soil was likely to be more sensitive to the addition of GLP and bioaugmentation than sandy soil.